A nanosheet-like BiPO4/Bi2O2CO3 heterostructured photocatalyst with enhanced photocatalytic activity. Issue 102 (2nd October 2015) - Liu, Yumin; Zhang, Peng; Lv, Hua; Guang, Jing; Li, Shuang; Jiang, Juhui
Abstract : The as-formed BiPO4 /Bi2 O2 CO3 heterojunction structure can facilitate interfacial charge transfer, thereby resulting in enhanced photocatalytic activity. Abstract : A nanosheet-like BiPO4 /Bi2 O2 CO3 heterostructured photocatalyst with different amounts of BiPO4 contents was successfully synthesized by the hydrothermal method. The photocatalytic activities of the BiPO4 /Bi2 O2 CO3 composite, pure Bi2 O2 CO3 and BiPO4 were evaluated by the photodegradation of rhodamine B (RhB) solution under UV light irradiation. The results demonstrated that all of the as-prepared BiPO4 /Bi2 O2 CO3 composites exhibited much higher photocatalytic activity than individual Bi2 O2 CO3 and BiPO4 . Among the composites, the 3% BiPO4 /Bi2 O2 CO3 showed the highest photocatalytic activity and the photodegradation efficiency of RhB could reach 92.6% within 40 min, which was about 1.7 and 2.3 times higher than that of pure Bi2 O2 CO3 and BiPO4, respectively. Simultaneously, the photostability and recyclability of 3% BiPO4 /Bi2 O2 CO3 were also investigated by four cycling runs for the photodegradation of RhB and the composite exhibited no significant loss of photocatalytic performance, confirming its long-time reusability. The enhanced photocatalytic activity of the BiPO4 /Bi2 O2 CO3 composite could be attributed to the formation of a suitable heterojunction structure, which facilitated interfacial charge transfer and improved the separation efficiency of photogenerated electron–hole pairs. Moreover, active species trapping experiments demonstrated that the holes (h + ) played key roles in RhB degradation. On the basis of experimental and theoretical calculation results, a possible reaction mechanism of the enhanced photocatalytic activity was proposed.